Online Counselling: Some Considerations for Existential-Phenomenological Practitioners (Existential Analysis: Journal of the Society for Existential Analysis, 2003)
The results of a phenomenological investigation of the experience of online counselling are set into the context of existential-phenomenological thought and practice, with a look at how time, space, embodiment, and discourse are altered online. In a recent investigation of the phenomenon, I elicited some fascinating descriptions of what it was like to be a counsellor online; however, I could find no co-researchers who identified themselves as existential-phenomenological counsellors. This required me to make a leap of imagination – that is, what issues *might* there be for an existential-phenomenological practitioner deciding to go online? In making that jump, I perhaps succeeded only in creating a whole new set of presuppositions, as yet unexplored due to the scarcity of online existential-phenomenological research participants, and besides, each counsellor influenced by the existential-phenomenological tradition would likely have a unique perspective on the phenomenon and an opinion about its appropriateness for them. Therefore, I make no 'for' or 'against' judgements; instead I examine what emerges when the research is set into the context of existential-phenomenological thought and practice. One of the major concerns of the co-researchers was the translation of their theories and skills into the online arena. Those of a psychodynamic bent struggled with how or whether interpretation, transference, and countertransference would 'work' online; those from a more person-centred tradition mentioned congruence, empathy, mirroring, and reflection. Half of the co-researchers specifically referred to being 'deskilled' or without 'technique' in the beginning and having to develop new kinds of skills as they progressed. So, would the existential-phenomenological counsellor also be 'deskilled' when embarking on online work? Numerous authors have described the existential-phenomenological approach as anti-technique and even anti-theory (van Deurzen-Smith, 1995; Spinelli, 1996; Heaton, 1995). Although the value of training, theoretical knowledge, and acquaintance with various 'skills' is not entirely dismissed, existential-phenomenological practitioners tend to be 60 Online Counselling more concerned with their ability to be present with the client, to 'be with' and 'be for' them so that the client's truths can be disclosed and discovered (Spinelli, 1994). So, if existential counselling is not about 'doing skills' but is rather about the therapist's qualities of being, how is being-with and being-for the client challenged or facilitated online? Here we have two parties engaged in (usually) asynchronous communication; although both are embodied in separate locations, they appear to one another in disembodied form as they access a 'virtual location.' Does this type of exchange constitute discourse? – that is, can those parties succeed in finding significance, sharing understanding, and giving expression to their human being-in-the-world (Myerson, 2001)?